PUBLIC FUNDS, PRIVATE GAINS: INVESTIGATING CORRUPTION IN NADRA’S MEGA CENTER LEASE DEALS - Siddiqui, Hassan Rasheed (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
This research investigates corruption and procedural violations in the National Database and Registration Authority (NADRA)’s procurement process for leasing Mega Centers in Sindh, with a particular focus on Mirpurkhas. The study examines serious allegations of favoritism toward an unqualified bidder, disregard for the lowest compliant bid, and the failure of NADRA’s senior management to address these irregularities. Employing a qualitative case study methodology, data were gathered through semi-structured interviews with 10 NADRA officials, 10 procurement officers, and representatives from bidding companies. In addition, documentary evidence—including procurement records, formal complaints, and internal communications—was analyzed to uncover inconsistencies and procedural breaches. Secondary sources such as investigative reports and news articles on corruption in public procurement were also used to contextualize the findings.The research identifies several critical issues: First, a non-compliant third bidder was awarded the contract due to procedural leniency, including acceptance of late documents and manipulation of site inspections. Second, the lowest bidder—who submitted the only compliant proposal—was unjustly disqualified, reflecting failures in the evaluation process. Third, despite formal complaints and verification payments, no meaningful action was taken, with the Chairman and NADRA’s management responding slowly or not at all, highlighting a lack of institutional accountability. Finally, the manipulation of the procurement process has significantly eroded public trust in NADRA and other government institutions involved.Based on these findings, the study proposes policy recommendations aimed at reforming NADRA’s procurement system. It underscores the urgent need for a robust institutional framework that ensures transparency, accountability, and fairness in future procurement practices.